Sorghum Breeding for Improved Drought Tolerance Using Induced Mutation with Gamma Irradiation - Soeranto Human Sihono (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2010)
<!– /* Font Definitions */ @font-face font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin-top:0cm; margin-right:0cm; margin-bottom:10.0pt; margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:Calibri; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; mso-ansi-language:IN; mso-no-proof:yes; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> Sorghum has a great potential to be grown and cultivated in Indonesia due to its wide adaptability and high productivity. Since sorghum is not a native species of Indonesia, the genetic variability of this crop in Indonesia is low, thus, plant breeding program is required to support national sorghum development. The objectives of this study were to develop superior genotypes to improve sorghum production and quality for food, animal feed and bioethanol industry. Sorghum production is aimed at optimal use of unproductive or marginal land such as that of drought prone areas. Sorghum breeding through induced mutations was conducted at Center for the Application of Isotope and Radiation Technology, National Nuclear Energy Agency (BATAN). Durra variety was used as parental materials in the breeding program. Induced mutation was made by gamma irradiation on seed treatments. The optimal radiation dose was found to be between 300-500 Gy. Through selection processes and direct screening for drought tolerance in Gunung Kidul district, ten putative mutant lines had been selected. In dry season, the mutant lines B-68, B-72, B-95 and B-100 produced grain yields of 4.55, 4.50, 4.20 and 4.62 ton ha-1, respectively. These yields were signiﬁ cantly higher than the original parent Durra (3.50 ton ha-1) and the control check varieties UPCA (2.68 ton ha-1) and Higari (3.75 ton ha-1). The mutant lines B-68, B-72, B-94, and B-100 were drought tolerant genotypes having a relatively higher drought index. These mutant lines were promising for further sorghum breeding and development in accordance with attempts of increasing land productivity of drought prone areas. Sorghum cultivation in such areas would promote land conservation and support sustainable agriculture development in the region. Keywords: drought tolerance, induced mutation, mutant lines, sorghum